Proposals of mathematical activities with a Bee-bot child robot based on STEM education (Edma 0-6: Educación Matemática en la Infancia, 2021)
This paper proposes a set of activities for students of first years of Chilean Primary Education in the area of mathematics, concentrated in geometry, and numbers and operations, through the incorporation of applied robotics in the classroom. The proposal of activities is bases on the manipulation of a robot called Bee- bot. This study is framed under STEM education, considered as a support tool in the teaching and learning process, guaranteeing a transversal work of skills and knowledge. In addition, it allows studying the concepts of educational robotics as a tool the enhance the skills and technical skills in the process of instruction in mathematics, encouraging the use of programming in technological environments and the development of computational thinking in students, as a way to develop the competence in problem solving.
Keywords: STEM Education; Mathematics; Educational robot; Bee-bot; Technology